2021
DOI: 10.1542/hpeds.2021-005994
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Resident Perspectives on the Impact of COVID-19 on Training

Abstract: OBJECTIVES At the onset of the coronavirus disease 2019 pandemic, disruptions to pediatric care and training were immediate and significant. We sought to understand the impact of the pandemic on residency training from the perspective of pediatric residents. METHODS We conducted a cross-sectional survey of categorical pediatric residents at US training programs at the end of the 2019–2020 academic year. This voluntary survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Our findings are supported by a survey-based study of 291 pediatric residency graduates from 2019 showing that over 50% of graduates entering the workforce perceived that their post residency employment was impacted by the COVID-19 pandemic. 4 It is unsurprising that a year later, and in light of the continued pandemic, pediatricians registering for the general pediatrics certifying examination, including many 2020 pediatric residency graduates, continued to indicate that their employment was affected by the pandemic. Studies from other residency specialties, such as surgery and plastic surgery, and pediatric subspecialties, such as pediatric gastroenterology, also indicate a negative impact on employment by the COVID-19 pandemic on some graduates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are supported by a survey-based study of 291 pediatric residency graduates from 2019 showing that over 50% of graduates entering the workforce perceived that their post residency employment was impacted by the COVID-19 pandemic. 4 It is unsurprising that a year later, and in light of the continued pandemic, pediatricians registering for the general pediatrics certifying examination, including many 2020 pediatric residency graduates, continued to indicate that their employment was affected by the pandemic. Studies from other residency specialties, such as surgery and plastic surgery, and pediatric subspecialties, such as pediatric gastroenterology, also indicate a negative impact on employment by the COVID-19 pandemic on some graduates.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has disrupted healthcare broadly, including the training of over 9,100 categorical pediatric residents across 212 training programs in the United States. 1 , 2 , 3 , 4 In both inpatient and outpatient settings, clinical volumes dropped dramatically during the pandemic, resulting in fewer in-person patient encounters, a change in the range of diagnoses seen, and, at some programs, redeployment to care for adults. 3 , 5 , 6 , 7 Hospital financial constraints due to decreased patient volume, 8 , 9 potential attrition of physicians retiring early, 10 and the pediatric subspecialty deficit may have impacted potential positions available during the pandemic, and, in turn, may have impacted career and employment decisions of pediatricians entering the workforce.…”
mentioning
confidence: 99%
“…Research describing the impact of the COVID-19 pandemic on trainee experiences and competencies is beginning to materialize [ 1 – 6 ]. Studies have indicated similar trends of decreased clinical exposures and training, regardless of specialty, including redeployments, cross-coverage for sick call, outpatient clinic cancellations, fewer inpatient shifts, and increased telemedicine encounters [ 1 , 3 , 6 8 ]. Decreased visits coupled with trainee redeployment from usual rotations have resulted in decreased clinical exposure [ 1 – 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated similar trends of decreased clinical exposures and training, regardless of specialty, including redeployments, cross-coverage for sick call, outpatient clinic cancellations, fewer inpatient shifts, and increased telemedicine encounters [ 1 , 3 , 6 8 ]. Decreased visits coupled with trainee redeployment from usual rotations have resulted in decreased clinical exposure [ 1 – 3 ]. Formal educational activities were also impacted due to shifts in clinical needs, social distancing regulations, and resident illnesses, requiring programs to quickly act to reformat their educational programs and utilize virtual tools in an attempt to preserve their existing curricula [ 1 , 4 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation